DINAMIKA KEPEMIMPINAN TRANSFORMASIONAL DALAM PENDIDIKAN DASAR PADA ERA SOCIETY 5.O: SEBUAH NARRATIVE REVIEW - Nur Elih; Nita Andriani; Fuad Abdul Baqi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
TheSociety 5.0 era brings rapid social and technological changes that require elementary schools to continuously adapt. In this context, school principals play a strategic role as leaders of educational change. This article examine the dynamics of transformational leadership in elementary education during the Society 5.0 era, focusing on its roles, impacts, and implementation challenges. A narrative review method was applied by analyzing relevant journal articles published within the last five years. The findings indicate that transformational leadership support school organizational change, enhances teachers professionalism and motivation, strengthens collaborative culture, and promotes technology-bases instructional innovation. However, its implementation faces challenges such as administrative workload, resistance to change, limited resources, and gaps in educators digital competencies. Therefore, policy support and leadership capacity development are essential to ensure the effective implementation of transformational leadership in elementary education.